Kandungan Minyak Esensial Sebagai Bahan Baku Obat-Obatan dari Tanaman Gaharu (Gyrinops versteegii) pada Kondisi Lahan Berbeda - ADNYANA, I MADE; MEGA, I MADE; ADI, I GUSTI PUTU RATNA (Agrotrop : Journal on Agriculture Science; Vol 12 No 1 (2022)DO - 10.24843/AJoAS.2022.v12.i01.p03, 2022)
Content of Essential Oils as Raw Materials for Medicine from Agarwood Plants ( Gyrinops versteegii ) in Various Soil Conditions . Essential oil is one of the processed agarwood ( Gyrinops versteegii ) which is useful in the basic ingredients of perfume, cosmetics, and medicines. The purpose of this study was to determine the volume and chemical composition of essential oils in agarwood plants in different land conditions. This research was conducted through a hydrodestillation process and chemical component analysis using a Gas Chromatography Mass Spectrophotometer (GCMS). The materials used are samples of agarwood from different lands, namely: A (agarwood on land with Regosol in Klungkung Regency) and B (agarwood on land with Latosol in Tabanan Regency). The specimens of agarwood consisted of: (1) Sapwood, (2) Kemedangan . The results showed that the essential oil content of the sapwood and kemedangan agarwood from Tabanan was higher than that of the sap and kemedangan agarwood from Klungkung. The composition of the compounds contained in sapwood includes: 9-Octadecenoic acid, Trans-13-Octadecenoic acid, Eugenol, 1-Nonadecene, Propanedioic acid, phenyl-; 2-propanol, 1,1'-oxybis-; 1-Propanol, 2- (2-hydroxypropoxy); Cyclopentadecanone, 2-hydroxy-and Oleic acid.